Development of Instrument Based on The Higher Order Thinking Skills (HOTS) to Practice of Critical Thinking Ability of High School Students on The Motions Systems Material - Eka Wahyu Putri M. Ritonga; Ummi Nur Afinni Dwi Jayanti (Universitas Labuhanbatu, 2024)
This research aims to develop a valid and practical Higher Order Thinking Skills (HOTS)-based instrument that is used to measure or train students' critical thinking abilities. The research uses the Bord and Gall model research and development (R&D) method. The research instruments are validation sheets (validation sheets from instrument experts and evaluation experts), questionnaires (teacher responses), and tests (effectiveness). The Second grade students (Class XI MIPA) of senior high school SMA Gajah Mada as subjects. Testing was carried out on student and biology teachers as respondents for the practicality of the module using student and biology teacher response questionnaire sheets. Based on the results of material expert validation, it was found that the expert validator's evaluation demonstrated the validity of the instrument by classifying it as appropriate for use based on an analysis of the material, construction, and linguistic aspects. This instrument also meets the reliability criteria. Multiple choice questions have a medium level of difficulty, good discriminating power